ERβ activation in obesity improves whole body metabolism via adipose tissue function and enhanced mitochondria biogenesis. (5th January 2019) - González-Granillo, Marcela; Savva, Christina; Li, Xidan; Fitch, Mark; Pedrelli, Matteo; Hellerstein, Marc; Parini, Paolo; Korach-André, Marion; Gustafsson, Jan-Åke
Abstract: Objective: Estrogens play a key role in the distribution of adipose tissue and have their action by binding to both estrogen receptors (ER), α and β. Although ERβ has a role in the energy metabolism, limited data of the physiological mechanism and metabolic response involved in the pharmacological activation of ERβ is available. Methods: For clinical relevance, non-ovariectomized female mice were subjected to high fat diet together with pharmacological (DIP - 4-(2-(3, 5-dimethylisoxazol-4-yl)-1H-indol-3-yl)phenol) interventions to ERβ selective activation. The physiological mechanism was assessed in vivo by magnetic resonance imaging and spectroscopy, and oral glucose and intraperitoneal insulin tolerance test before and after DIP treatment. Liver and adipose tissue metabolic response was measured in HFD + vehicle and HFD + DIP by stable isotope, RNA sequencing and protein content. Results: HFD-fed females treated with DIP had a tissue-specific response towards ERβ selective activation. The metabolic profile showed an improved fasting glucose level, insulin sensitivity and reduced liver steatosis. Conclusions: Our data demonstrate that selective activation of ERβ exerts a tissue-specific activity which promotes a beneficial effect on whole body metabolic response to obesity. Graphical abstract: Image 1 Highlights: DIP is a selective ERβ ligand. ERβ activation exerts a tissue-specific activity. DIP ligand remodels body lipid distribution improving metabolic profile. DIP administration decreases total mass of VAT and SAT. ERβ activation tends to induce browning in VAT and preserved BAT activity.